Supramolecular dielectric polymer material, preparation method and application thereof
By designing supramolecular dielectric polymers with helical structures and regulating the polymer structure using hydrogen bond networks, the leakage current problem of high-temperature dielectric polymer materials under high temperature and high electric fields is solved, and efficient high-temperature energy storage performance is achieved.
Patent Information
- Application Number
- CN202410567674.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-08
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-05-08
AI Technical Summary
The leakage current of existing high-temperature resistant dielectric polymer materials increases dramatically under high temperature and high electric field conditions, resulting in increased conductivity loss, decreased breakdown field strength and charge and discharge efficiency, which seriously affects its energy storage performance.
By designing and preparing supramolecular dielectric polymers with helical structures, using hydrogen bond interactions to form a hydrogen bond network, regulating the stacking method of polymer structural units, eliminating planar conjugation and π-π stacking, thereby suppressing leakage current.
It achieves low leakage current under high temperature and high electric field conditions, improves the high-temperature energy storage performance of dielectric polymers, and the leakage current of the material at 200℃ is 3.2*10-9A/cm2, the breakdown field strength is 538MV/m, and the energy storage density is 9.85J/cm3, meeting the requirements of high-temperature energy storage.
Smart Images

Figure CN118421084B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer dielectric materials, and in particular to supramolecular dielectric polymer materials, preparation methods and applications thereof. Background Art
[0002] As the core supporting technology for the development of new energy, energy storage technology has been widely used in many fields such as the grid side, user side and social functional energy storage facilities. Among many energy storage devices, dielectric energy storage capacitors occupy an important position in the modern electronic power industry due to their extremely fast energy conversion rate (capable of achieving microsecond-level discharge), excellent temperature stability and strong fatigue resistance. In particular, dielectric film capacitors made of polymer dielectric materials represented by biaxially oriented polypropylene film (BOPP) are widely used due to their excellent high-voltage resistance, extremely low dielectric loss, good flexibility and self-healing properties.
[0003] However, with the rapid development of new energy vehicles and aerospace vehicles, the demand for high-temperature applications of dielectric energy storage film capacitors has become increasingly urgent. It needs to be able to operate at temperatures above 140°C, which is far beyond the operating temperature limit of current commercial BOPP dielectric film capacitors. Aromatic dielectric polymer materials with aromatic rings, such as polyimide (PI), polyetherimide (PEI) and meta-aromatic polyurea (ArPU), have a high glass transition temperature (T g ), excellent heat resistance and mechanical properties have attracted much attention. However, under high temperature and high electric field conditions, the leakage current of these high temperature resistant dielectric polymer materials will increase dramatically due to the excitation, injection and transmission of hot carriers, resulting in increased conductivity loss, reduced breakdown field strength and charge and discharge efficiency, which seriously affects their energy storage performance. At present, there is no literature on the use of PI and meta-aromatic polyurea (Mt-PU) to prepare dielectric polymer materials. Therefore, how to effectively suppress the leakage current of dielectric polymer materials under high temperature and high electric field has become the core challenge to improve the high temperature energy storage performance of dielectric capacitors, which has important scientific significance and practical application value in the fields of new energy vehicles, aerospace and energy storage.
[0004] In order to solve the huge conductivity loss problem of traditional heat-resistant polymer dielectric materials under high temperature and high electric field, researchers at home and abroad have designed a variety of new materials through different strategies. These materials are mainly divided into two categories: non-intrinsic dielectric polymer composites and intrinsic dielectric polymers. Non-intrinsic dielectric polymers are mainly formed by incorporating inorganic particles, organic small molecules or nanomaterials into organic polymers to form composite materials. For example, by adding trace amounts of alumina inorganic nanofillers to the organic polymer polyaryletherurea (PEEU), the interface interaction between inorganic nanoparticles and the polymer matrix is utilized to form deep traps in the interface region, thereby achieving excellent high-temperature energy storage characteristics. Yang et al. prepared PEI sub-nanocomposites by doping phosphotungstic acid sub-nanosheets with a thickness of less than 1 nm into the PEI matrix. These sub-nanosheets have a large specific surface area and produce a huge interface area in PEI, thereby ensuring the number of carrier traps. The above literature proves that non-intrinsic dielectric polymers can effectively suppress leakage current, but the agglomeration of fillers is a common problem, which may damage the flexibility, uniformity and processability of dielectric polymer films, thereby increasing the cost of large-scale production. On the other hand, intrinsic dielectric polymers suppress leakage current by regulating the intrinsic structure of the polymer, such as introducing polar groups, adjusting molecular segments, preparing cross-linked structures and polymer blending. For example, Liu et al. introduced polar groups —COOH and —CO-NH- into PI, so that the polar groups on the benzene ring were retained as carrier traps. The above results prove that these methods suppress leakage current to a certain extent, but the π-π stacking effect caused by the conjugated benzene ring structure is still a challenge. High-temperature resistant polymers with conjugated aromatic skeletons all have a π-π stacking effect formed by the conjugated benzene ring structure of the main chain of aromatic polymer molecules, and transmission along the π-π stacking direction is the main mode of carrier transmission in the conjugated molecular system. This stacking effect will reduce the band gap of the material, resulting in an increase in its leakage current. Therefore, how to effectively eliminate the leakage current caused by π-π stacking while maintaining high temperature resistance has become the key to the design of high-temperature energy storage dielectric polymer films. Summary of the invention
[0005] In order to solve the problems caused by conjugated aromatic structures, the present invention proposes a simple and flexible supramolecular chemical method, which aims to design and prepare a novel non-planar high temperature resistant dielectric polymer. By using two or more molecules through intermolecular non-covalent interactions (such as hydrogen bonds, van der Waals forces, electrostatic effects, halogen bonds, etc.), a helical structure molecular aggregate is formed. Specifically, the strongest hydrogen bonding force in the intermolecular non-covalent interaction force is used as the driving force, and the synergy of multiple hydrogen bonds is used to construct a hydrogen bond network. By carefully designing the molecular structure and co-assembly unit of the existing high temperature resistant dielectric polymer, the stacking mode of different polymer structural units can be flexibly regulated at the supramolecular level. In the self-assembly process, these structural units can be spontaneously and orderly transformed into a helical structure, thereby forming a non-planar supramolecular dielectric polymer. This structure can eliminate planar conjugation and π-π stacking, thereby suppressing the leakage current of the dielectric polymer.
[0006] In view of this, the scheme of the present invention is as follows:
[0007] In a first aspect of the present invention, a supramolecular dielectric polymer material is provided, which is made of meta-aromatic polyurea and polyimide, wherein the mass of the meta-aromatic polyurea accounts for 10 to 40% of the total mass of the meta-aromatic polyurea and the polyimide; the meta-aromatic polyurea and the polyimide have the structural formulas shown in formula (I) and (II), respectively:
[0008]
[0009] Furthermore, the mass ratio of the meta-aromatic polyurea is 15-35%, preferably the mass ratio of the meta-aromatic polyurea is 20-30%, and more preferably the mass ratio of the meta-aromatic polyurea is 25%.
[0010] Preferably, when the mass ratio of meta-aromatic polyurea is 25%, the leakage current of the material at 200°C is 3.2*10 -9 A / cm 2 , E b 538MV / m, U d 9.85 J / cm 3 , which can meet the energy storage requirements under high temperature and high electric field conditions.
[0011] The second aspect of the present invention provides a method for preparing the supramolecular dielectric polymer material of the first aspect, comprising mixing meta-aromatic polyurea and polyimide, and casting the mixture into a film through solution casting to obtain the supramolecular dielectric polymer material.
[0012] Furthermore, the preparation method is specifically as follows: coating a mixed solution of meta-aromatic polyurea and polyimide on a substrate, heating to remove the solvent, curing, annealing and peeling off the substrate to obtain a supramolecular dielectric polymer material.
[0013] Preferably, the solvent used in the mixed solution is DMF, the temperature of the solvent removal process is 60-80° C., and the curing temperature is 95-105° C. More preferably, the temperature of the solvent removal process is 70° C., and the curing temperature is 100° C.
[0014] Preferably, the coating method includes a brushing method, a spraying method, a casting method or a dipping and pulling method.
[0015] Preferably, the annealing temperature is 110-130°C, more preferably 120°C.
[0016] The third aspect of the present invention provides the application of the supramolecular dielectric polymer material described in the first aspect or the supramolecular dielectric polymer material prepared by the preparation method described in the second aspect in the field of high-temperature polymer dielectric energy storage materials.
[0017] In a fourth aspect of the present invention, a dielectric energy storage capacitor is provided, comprising the supramolecular dielectric polymer material described in the first aspect or the supramolecular dielectric polymer material prepared by the preparation method described in the second aspect. The capacitor comprises two electrode layers arranged opposite to each other and a dielectric layer sandwiched therebetween; the supramolecular dielectric polymer material is used as the dielectric layer.
[0018] Compared with the prior art, the beneficial effects of the present invention include but are not limited to:
[0019] 1. The present invention obtains a supramolecular dielectric polymer material by constructing meta-aromatic polyurea and polyimide, which has a helical structure and can eliminate planar conjugation and π-π stacking, thereby inhibiting the leakage current of the dielectric polymer and further improving the high-temperature energy storage performance of the dielectric polymer.
[0020] 2. The method for preparing supramolecular dielectric polymer materials of the present invention has strong universality, the raw materials are easily available, the film processing is simple, and the practical application in high-temperature electronics and energy storage devices is of great significance. It has important scientific significance and practical application value in the fields of new energy vehicles, aerospace and energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the structure of the polyimide (PI) and the helical supramolecular dielectric polymer (HSP) of the present invention.
[0022] Figure 2 This is the simulation calculation process of the helical structure supramolecular dielectric polymer (HSP) described in the present invention.
[0023] Figure 3 This is a real picture of the helical structure supramolecular dielectric polymer (HSP) film prepared in an example of the present invention.
[0024] Figure 4This is the characterization result of the HSP-25% composite film prepared in the example of the present invention.
[0025] Figure 5 This is the energy band comparison result of the HSP-25% composite film prepared in the embodiment of the present invention and PI and Mt-PU. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with specific implementation methods. It should be understood that the specific implementation methods described in this specification are only for explaining the present invention, not for limiting the present invention.
[0027] In one embodiment, the strongest hydrogen bonding force among the intermolecular non-covalent interactions is used as the driving force, and the synergy of multiple hydrogen bonds is used to construct a hydrogen bonding network. By carefully designing the molecular structure and co-assembly units of the existing high temperature resistant dielectric polymers, the stacking mode of different polymer structural units can be flexibly controlled at the supramolecular level. During the self-assembly process, these structural units can spontaneously and orderly transform into a helical structure, thereby forming a non-planar supramolecular dielectric polymer, such as Figure 1 This structure can eliminate planar conjugation and π-π stacking, thereby suppressing the leakage current of the dielectric polymer.
[0028] The strength of hydrogen bonds in supramolecular polymers can be well designed and controlled, so hydrogen bonds are ideal non-covalent bonds for forming supramolecular polymers. Meta-aromatic polyurea (Mt-PU) is a strong dipole with a relatively high K (~5) and low loss (<1%). g ) polymer. In one embodiment, it is considered to introduce Mt-PU into PI to adjust the helical configuration in HSP, and Mt-PU and PI have the structural formulas shown in formula (I) and (II), respectively:
[0029]
[0030] like Figure 2 As shown in the figure, molecular dynamics simulation utilizes the synergistic effect between multiple C=O bonds in PI and multiple NH bonds in PU to form multiple hydrogen bonds, which are then assembled into a dense and ordered high-density hydrogen bond synergistic network. This multiple hydrogen bond synergistic network enhances the synergy and average bond energy of hydrogen bonds. Driven by multiple hydrogen bonds, the two molecular chains are entangled with each other to form a unique double helix structure. This three-dimensional double helix structure effectively breaks the planar morphology and π-π stacking of meta-aromatic polymer materials. The half pitch of the double helix is The helicity is 0.8 (PI:Mt-PU = 0.8). The calculation results show that the molecular chains of PI and Mt-PU can be connected by multiple bonds with shorter lengths (approx. ), strong hydrogen bonds (15.5 kJ / mol) form a multiple hydrogen bond cooperative network, thereby stabilizing the double helix structure and reducing the intermolecular π-π stacking energy from 18.3 kJ / mol of PI to 0.8 kJ / mol of HSP. In addition, the results of flexible scanning calculations show that when the dihedral angle of the two molecules forms 60°, the system energy reaches the lowest, indicating that the structure has good stability.
[0031] In a preferred embodiment, the meta-aromatic polyurea (Mt-PU) of formula (I) can be prepared by reacting meta-phenylenediamine with diphenyl carbonate in a VAC solvent at 100° C. The PI of formula (II) is commercially available (www.piezopvdf.com).
[0032] Example
[0033] Prepare 0.2wt% PI solution and 0.2wt% Mt-PU solution, both of which are DMF solvents, place on a turntable and rotate for 12 hours to ensure full dissolution, then mix and shake the 0.2wt% PI solution and 0.2wt% Mt-PU solution, and prepare mixed solutions of different proportions, such as HSP-10% (the mass ratio of PI:Mt-PU is 90:10), HSP-15%, HSP-20%, HSP-25%, HSP-30%, HSP-35%, HSP-40%. Drop on a glass plate by casting, place the glass plate in an oven, heat at 70°C for 12 hours to remove the solvent, heat at 100°C for 12 hours to solidify into a film, and anneal at 120°C for 24 hours to obtain an HSP composite film.
[0034] The formed HSP (7×5cm 2 ) Composite film such as Figure 3 As shown in the figure, a is in the stretched state, and b is in the curled state. It is obvious that the HSP composite film has good toughness and has the prospect of large-scale production.
[0035] Performance testing and characterization
[0036] 1. Mechanical properties test
[0037] The HSP prepared in the above examples with different Mt-PU addition ratios were tested for mechanical properties. The results are as follows: Figure 1 As shown,
[0038] Table 1. Mechanical properties of films with different ratios at 25°C
[0039]
[0040] From Table 1, it can be seen that compared with PI and Mt-PU alone, the performance of HSP in all aspects is improved. Preferably, Mt-PU addition amount of 20-30%, more preferably HSP-25%, has the best mechanical properties.
[0041] 2. Structural Characterization
[0042] The morphology of the self-assembled structure in HSP-25% was observed under scanning electron microscopy (SEM). Figure 4 a, 4b), SEM showed that the molecules of HSP-25% had aggregated into a double helix with a diameter of about 200nm and a pitch of about 410nm. Fluorescence testing showed that the π-π stacking between molecules in HSP-25% was weakened ( Figure 4 c), which means that the double helix structure destroys the original planar structure, leading to the formation of hydrogen-bonded segments with multiple hydrogen-bonding sites in a three-dimensional structure. Due to their high flexibility, these hydrogen-bonded segments can be assembled into a dense, ordered, high-density hydrogen-bonded array, thereby significantly enhancing the synergy of hydrogen bonds.
[0043] 3. Dielectric performance test
[0044] In order to evaluate the effect of the double helix structure on the dielectric properties of HSP composite films, the dielectric properties of HSP composite films with different proportions of Mt-PU were tested at 25°C and 1kHz. The results are shown in Table 2.
[0045] Table 2. Dielectric properties of films with different ratios at 25°C
[0046]
[0047] It can be seen from Table 1 that with the increase of the mass proportion of Mt-PU, the dielectric constant of the HSP composite film gradually increases, and HSP-25% achieves a dielectric constant of up to 7.3 and an extremely low dielectric loss of 0.2% at 25°C and 1kHz. Compared with pure PI and Mt-PU, the dielectric constant has been significantly improved by 121.2% and 40.4%, respectively. When the mass proportion of Mt-PU is further increased, the dielectric constant of the HSP composite film shows a downward trend.
[0048] The dielectric properties at other temperatures were further tested at frequencies of 1kHz-1 MHz, and the results are shown in Table 3-5.
[0049] Table 3. Dielectric properties of HSP composite films with different ratios at 100°C
[0050]
[0051] Table 4. Dielectric properties of HSP composite films with different ratios at 150°C
[0052]
[0053] Table 5. Dielectric properties of HSP composite films with different ratios at 200°C
[0054]
[0055]
[0056] It is not difficult to see from Table 2-5 that the high K and low dielectric loss of HSP-25% remain stable in the temperature range of 25-200°C and the frequency range of 1kHz-1MHz.
[0057] To further evaluate the effect of the double helix structure on the electrical properties, the UV-visible spectra (UV-Vis) were measured and compared with those of PI and Mt-PU, e.g. Figure 5 As shown in the figure, the band gap (E g ) is 4.23 eV, which is much higher than PI (3.13 eV) and Mt-PU (3.25 eV), which is due to the reduction of conjugated structure. This shows that the combination of double helical structure and non-planar segment helps to improve the E of HSP-25%. g From the dielectric properties test results, it is known that with the increase of the mass proportion of Mt-PU, the breakdown field strength of the HSP composite film gradually increases, and the breakdown field strength of HSP-25% at 25°C reaches 825MV / m, which is far higher than PI and Mt-PU. As the Mt-PU content further increases to more than 25%, E b The sudden decrease in is obviously attributed to the destruction of the ordered structure.
[0058] In addition, the dielectric properties test results show that the leakage current of pure PI, Mt-PU and HSP with different proportions at 300MV / m, compared with PI, with the increase of Mt-PU proportion, the leakage current of HSP gradually decreases, and the leakage current of HSP-25% reaches the lowest (1.2×10 -10 A / cm 2 ), which shows that the addition of Mt-PU has good insulation properties. As the proportion of Mt-PU increases further, the leakage current gradually increases, which is consistent with the trend of the breakdown field strength. At the same time, the leakage current density results can verify the increase of the double helix structure band gap.
[0059] 4. High temperature energy storage
[0060] From the room temperature dielectric properties, it can be seen that when the mass ratio of PI:Mt-PU is 75%:25%, the dielectric constant (7.3) and breakdown field strength (825MV / m) of the HSP composite film reach the maximum value, while the leakage current reaches the minimum value (1.2×10 -10 A / cm2 ), so we believe that HSP-25% is the best ratio for the composite film. At the same time, it can be seen from Tables 3-5 that this trend is still met at 100℃, 150℃, and 200℃. The energy storage performance of HSP-25% at different temperatures and different ratios is shown in Tables 2-5. When η is greater than 90%, HSP-25% exhibits the best high-temperature energy storage performance. For example, at 100℃, U d 17.07 J / cm 3 ,U at 650MV / m at 150℃ d 15.35 J / cm 3 , at 200℃, U at 538MV / m d 9.85 J / cm 3 , which is at least one order of magnitude higher than that of pure PI. These results demonstrate the excellent energy storage performance of HSP-25% at high temperatures. It is worth noting that from 25℃ to 200℃, the U d It gradually decreases (η>90%), showing good heat resistance, while the η of pure PI and Mt-PU decreases sharply at 150℃ and 200℃.
[0061] In summary, the high-temperature energy storage performance of dielectric polymers is improved by adjusting the leakage current of dielectric polymers. By adjusting the combination of different ratios between PI and Mt-PU, the dielectric constant, breakdown field strength, and energy storage density can be further improved, and large-area, high-quality films with uniform dielectric and capacitive properties can be prepared. In addition, the method is highly universal. Since the raw materials are readily available and the film processing is simple, this all-organic composite strategy is of great significance for its successful commercialization and practical application in high-temperature electronics and energy storage devices. It has important scientific significance and practical application value in the fields of new energy vehicles, aerospace, and energy storage.
[0062] The present invention is not limited to what is described in the specification and implementation modes, and therefore additional advantages and modifications can be easily realized by those skilled in the art. Therefore, without departing from the spirit and scope of the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details, representative schemes, and examples described herein.
Claims
1. A supramolecular dielectric polymer material, characterized in that: It is prepared from meta-aromatic polyurea and polyimide, wherein the mass of the meta-aromatic polyurea accounts for 20-30% of the total mass of the meta-aromatic polyurea and the polyimide; the meta-aromatic polyurea and the polyimide have the structural formulas shown in formula (I) and (II) respectively: , 。 2. The supramolecular dielectric polymer material according to claim 1, characterized in that: The mass proportion of the meta-aromatic polyurea is 25%.
3. The supramolecular dielectric polymer material according to claim 2, characterized in that: The leakage current of the material at 200 °C is 2.4×10 -7 A / cm 2 , E b is 538 MV / m, U d 9.85 J / cm 3 .
4. The method for preparing the supramolecular dielectric polymer material according to any one of claims 1 to 3, characterized in that: The meta-aromatic polyurea and polyimide are mixed and solution-casted to form a film to obtain the material.
5. The preparation method according to claim 4, characterized in that: The material is obtained by coating a mixed solution of meta-aromatic polyurea and polyimide on a substrate, heating to remove the solvent, curing, annealing and peeling off the substrate.
6. The preparation method according to claim 5, characterized in that: The solvent used in the mixed solution is DMF; and / or the temperature of the solvent removal process is 60-80°C; and / or the curing temperature is 95-105°C.
7. The preparation method according to claim 5, characterized in that: The coating method includes a brushing method, a spraying method, a casting method or a dipping and pulling method; and / or the annealing temperature is 110-130°C.
8. Use of the supramolecular dielectric polymer material according to any one of claims 1 to 3 or the supramolecular dielectric polymer material prepared by the preparation method according to any one of claims 4 to 7 in the field of high-temperature polymer dielectric energy storage materials.
9. A dielectric energy storage capacitor, characterized in that: The invention comprises the supramolecular dielectric polymer material according to any one of claims 1 to 3 or the supramolecular dielectric polymer material prepared by the preparation method according to any one of claims 4 to 7.
Citation Information
Patent Citations
Thin film capacitors
US20190035556A1